Establecimiento de relaciones alométricas para estimar la producción de biomasa en cultivares de cacao (theobroma cacao l.) tipo nacional desarrollados por la UTEQ - Chagerben Vallejo, Adib Carlos (2017)
Ecuador is recognized as one of the best cocoa producers in the world because it has a unique type of cocoa that is the "National". The national cocoa is characterized to obtain its fermentation in a very short time and therefore when processed, it provides a chocolate with a delicious flavor and aroma, the same one that is internationally recognized and classified as "Fine Cocoa of Aroma". The national cacao for two centuries is cultivated in the areas of the upper basin of the Daule and Babahoyo Rivers, which form the Guayas River on the banks of which is the city of Guayaquil, the main port of Ecuador and from where they are made to date all exports of cocoa. The present study evaluated the functional relationship between length measures of vegetative structures and biomass in cacao cultivars National Type; In addition, the functional relationship between the surface measurements of the structures and the functional relationship between the volume measurements was evaluated, thus obtaining the biomass contents of the different vegetative structures of each tree evaluated, where it was determined that there were very few differences marked between the biomass content of the trunk of the studied trees. The total biomass of the tree presented a standard deviation of 5,68 while the biomass contained in the trunks was presented in a more uniform way, obtaining a standard deviation of 0,48. The statistical variables (p <0,05) showed statistically significant differences among the clones evaluated. The normal diameter (dn) obtained reflects that the cocoa clone of national origin L40H49 obtained the highest dn with 16,69 cm, while the lowest dn was obtained by the clone L30H07; the coefficient of variation was 7,34. The variable dn2 is related to dn, where it is observed that clone L40H49 obtained 278,68 cm2 while clone L30H07 achieved 78 cm2. The relationship between the dasometric variables and the biomass content shows the relationship between dn and the total biomass, the equation adjusted to Y=2,1723x-19,62 can be observed and the coefficient of determination was 0,75; the relationship between dn2 and the biomass content is also shown, where the equation adjusted to Y=0,0851x-6,25 is shown and the coefficient of determination reaches a value of 0,78.